Thinking Style Pattern Among Design and Technology Teachers in Malaysia - Shanty, Saien; Kiong, Tee Tze; Jailani, Md Yunos; Heong, Yee Mei; Mimi Mohaffyza, Mohamad; Widad, Othman; Mohamed Nor Azhari, Azman; Zaliza, Hanapi; Nurulwahida, Azid (Journal of Technical Education and Training, 2018)
Critical and creative thinking skills are vital in new Malaysia curriculum starting 2011. These skills are advised to be integrated in all subjects in school. Hence, knowing the teachers thinking style can be an advantage as this can give the impression on how the students will be. This study was conducted to identify the tendency to which creative critical thinking style of Design and Technology (DT) teachers across Malaysia. A total of 367 teachers are involved and required to answer the instrument known as YPCreative-Critical Test which consist of 34 items. This instrument was develop using Google Form and been send out to the respondent through email, Facebook, WhatsApp, Telegram and Instagram application to ease the teachers to respond online. The data then analyzed using descriptive statistic and inferential statistics. The finding from this study showed that nearly half of the DT teachers having balance thinking style. Creative thinking style has 35.4% of the total while critical thinking style 19%. None of our teachers has superior thinking style. The independent t-test result shows there is no significant difference thinking styles among DT teachers in gender.